Effects of sub-lethal exposure of rats to the herbicide glyphosate in drinking water: Glutathione transferase enzyme activities, levels of reduced glutathione and lipid peroxidation in liver, kidneys and small intestine - Larsen, Karen Elizabeth (2012)
Glyphosate (GLP), the active ingredient of many weed killing formulations, is a broad spectrum herbicide compound. Wistar rats were exposed during 30 or 90 days to the highest level (0.7. mg/L) of GLP allowed in water for human consumption (US EPA, 2011) and a 10-fold higher concentration (7. mg/L). The low levels of exposure to the herbicide did not produce histomorphological changes. The production of TBARS was similar or tended to be lower compared to control animals not exposed to the herbicide. In rats exposed to GLP, increased levels of reduced glutathione (GSH) and enhanced glutathione peroxidase (GPx) activity may act as a protective mechanism against possible detrimental effects of the herbicide. Overall, this work showed certain biochemical modifications, even at 3-20-fold lower doses of GLP than the oral reference dose of 2. mg/kg/day (US EPA, 1993). The toxicological significance of these findings remains to be clarified.